Joint Vibrations Analysis in Asymptomatic Volunteers and Symptomatic Patients - Olivieri, Karina Andrea Novaes [UNESP]; Garcia, Alício Rosalino; Paiva, Guiovaldo; Stevens, Christopher (Taylor & Francis, 1999)
The joint sound is a common sign in TMD. The diagnosis is important to establish the treatment of pathological alterations which occur in the TMJ. In this study, two groups were selected: 1. Asymptomatic volunteers; and 2. Symptomatic patients who were diagnosed in a clinical examination. After the initial examination, they were submitted to evaluation using electrovibratography (SonoPAK II, BioResearch Assoc., Inc., Milwaukee, Wisconsin). The analysis of results indicated that the averages of the vibratory energy in the symptomatic group presented higher values in all stages of the mandibular movement when compared to the averages of vibratory energy registered in the asymptomatic group.